Companion planting: the effect of planting Allium Cepa (onion plant) to the growth of Capsicum Annuum (chili plant) / Nur Shahira Abdul Nasir - Abdul Nasir, Nur Shahira (2018)
The purpose of this research is to prove the method ‘companion planting’ or as known as ‘intercropping’ managed to improve the rate of growth for the plants involved. The purpose of the study is to identify how the Allium cepa (onion plant) could bring effects to the rate of growth of Capsicum annuum (chili plant). In this research, the seeds of both plants are germinated separately. Every means of supporting the plant growth was by using organic manure. All the germinated seedlings were transferred into the study site. On the study site, there were two separate sets of plants. One of it was chili plant planted alone in a row of three while the other set was chili plant planted next to onion plant, which also planted in a row of three. Each row contained five plants. The growth process of the chili plant is observed carefully and comparison was made between the two sets of plants. The parameters which were being observed are the height, number or leaves, number of primary branches and dry weight. The p-value (>0.05) obtained from data analysis proves that there is no significance difference between the intercrop group and the sole crop group.